Lyric Scholarship in Controversy: - Northrup, Tina (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2012)
Counted among Canada’s most influential poet-scholars of the late twentieth and early twenty-first centuries, Jan Zwicky and Anne Carson challenge the conventional distinctions that separate classical scholarship, art criticism, philosophy, and poetry. Although seldom paired by criticis, their scholarly and creative methods are comparable, serving as examples of lyric – a term that, through Zwicky’s work especially, signifies a contemporary movement in which poets and scholars resist what they see as prescriptive and unethical programs for academic pursuit. By allowing diverse genres of research and writing to infiltrate their writings, Carson and Zwicky have helped bring the political assumptions and cultural ramifications of certain academic conventions to light. Notably, in two controversial critiques of these writers and their work, David Solway and Zach Wells implicitly attribute the lyric approach to a markedly feminine and naive intellectual stance. Particularly in the contexts provided by Carson’s and Zwicky’s writings, such perspectives betray deep-seated gender prejudices that hinder Canada’s artistic and intellectual future.